Menyingkap Peradaban Islam Kontemporer di Anak Benua India - Asrori, Mohammad (UIN Maulana Malik Ibrahim Malang, 2009)
Civilization and culture in the arm of the continent of India had undergone the rise and fall since the colonialism era until the independence day. It can be illustrated by the domination of political map which had existed since the arrival of foreign nation, especially England until they got their indepence. The condition of Indian society at that time was full of contradiction, religion coflicts, quarrelling, robbery, various race, certain group interest dominating, and etc. From this condition, it born many great islamic political figures like Syeh Ahmad Sirhindi, Shah Waliyullah and the next generation, Sayyid Ahmad Khan and the next generation, Indian Moslem League. Which finally made India and Pakistan Independence (1947 M) and Bangladesh’s (1971M). Next, these three countries, which are the same in term of historical country have also various dynamic and sophisticated improvement of Islam. Peradaban dan budaya di benua India telah mengalami kenaikan dan penurunan sejak era penjajahan hingga hari kemerdekaan. Hal itu bisa diilustrasikan dalam dominasi peta politik yang sudah ada sejak kedatangan bangsa asing, terutama Inggris sampai mereka mendapat indepence mereka. Kondisi masyarakat India saat itu penuh dengan kontradiksi, pertentangan agama, pertengkaran, perampokan, berbagai ras, minat kelompok tertentu yang mendominasi, dan lain-lain. Dari kondisi ini, lahirlah banyak tokoh politik islam seperti Syeh Ahmad Sirhindi, Shah Waliyullah dan generasi berikutnya, Sayyid Ahmad Khan dan generasi berikutnya, Indian Muslim League. Yang akhirnya membuat Kemerdekaan India dan Pakistan (1947 M) dan Bangladesh (1971M). Selanjutnya, ketiga negara ini, yaitu Hal yang sama dalam hal negara bersejarah juga memiliki berbagai pembaharuan Islam yang dinamis dan canggih.